1998
DOI: 10.1007/bf02831365
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy-exaggerated galactosemia and congenital cataracts

Abstract: One child in a family and two children in another family had galactosemia and congenital cataract. Two of them had total soft cataracts while in one, cataract was less soft. In addition, they had mild lactosuria. The mothers of the affected children had significant lactosuria and mild galactosuria without cataracts. Fathers did not have galactosuria or lactosuria. Clinically unaffected siblings in one family had mild galactosuria and lactosuria. Pregnancy-exaggerated galactosemia was suspected in these two mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…128 A study also observed that inositol displayed a potent antiglycative property (57-67% decrease of glycation of human eye lens proteins with glucose) due to the scavenging of glucose. 129 In addition, alterations of rat tail tendon collagen induced by glycation can be prevented by arginine and arginine-lysine. 130 In the presence of amino acids arginine and lysine, glucose incorporation into rat tail tendon fibers as well as Amadori product formation decreased significantly, which was mainly due to the competitive attachment of these two amino acids to glucose.…”
Section: Inhibition Of the Formation Of Agesmentioning
confidence: 99%
“…128 A study also observed that inositol displayed a potent antiglycative property (57-67% decrease of glycation of human eye lens proteins with glucose) due to the scavenging of glucose. 129 In addition, alterations of rat tail tendon collagen induced by glycation can be prevented by arginine and arginine-lysine. 130 In the presence of amino acids arginine and lysine, glucose incorporation into rat tail tendon fibers as well as Amadori product formation decreased significantly, which was mainly due to the competitive attachment of these two amino acids to glucose.…”
Section: Inhibition Of the Formation Of Agesmentioning
confidence: 99%